Kelelawar Sebagai Ide Penciptaan Seni Instalasi - Suarsana, I Kadek Doni (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2023)
This thesis raises the theme "bats as an idea for creating art installations." Starting from past memories when the author was still in grade V of Elementary School (SD) the writer and his friends played and caught small bats which are often called jempiit in the garden behind the house, after school the writer and friends took the time to play in the garden behind the house to catch or look for small bats (pinch). Bats are a member of the mammal group, and the only animals from this group that can fly. This capability, coupled with the ability to navigate at night using an acoustic orientation system (echolocation), makes bats an interesting animal. But there are some people who consider bats to be evil animals as in other places in the world, these flying mammals are often misunderstood. From the description above, the writer will make it happen by transforming bats into installation art, this work is made by the author using recycled materials such as used paper, coconut fiber, tissue, bamboo and cardboard.